Analisis Sistem Informasi Pengelolaan Data Atlet Sebagai Bagian Dari Implementasi Program Satu Data Sumsel Di Dinas Pemuda Dan Olahraga - Adit Adriyansa,; Ari Muzakir, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The implementation of the One Data Indonesia policy requires every government institution to manage data in an integrated, accurate, and accountable manner. The Department of Youth and Sports of South Sumatra Province is one of the institutions that has implemented this policy through the Satu Data Satu Digital Sumsel platform for athlete data management. This study aims to analyze the athlete data management information system as part of the implementation of the One Data Sumsel Program. The research method used is a qualitative descriptive approach with a case study design, complemented by SWOT analysis to evaluate the system’s strengths, weaknesses, opportunities, and threats. The results show that the web-based information system improves the efficiency of athlete data management, accelerates the data collection process, and supports data transparency and accuracy. However, several challenges remain, including dependence on internet connectivity, manual data entry processes, and limited automatic validation features. Therefore, continuous system development is necessary to optimize the implementation of the One Data Sumsel Program in the sports sector.